PERBEDAAN HASIL BELAJAR FISIKA SISWA MENGGUNAKAN STRATEGI PEMBELAJARAN INKUIRI DAN DISKOVERI DI SMA NEGERI 8 BANDA ACEH - Suci Mustika; Elisa Kasli; Abdul Hamid (Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2017)
This research entitles “The Difference of Learning result by Using Discovery and Inquiry Learning Strategy at SMA Negeri 8 Banda Aceh”. It was aimed to look into the difference of students’ learning result in Class XI at SMA Negeri 8 Banda Aceh through the implementation of Discovery and Inquiry learning strategy. This research is a quasi experimental study with all students of Class XI at SMA Negeri 8 become the population. While the sample of this research was chosen by using purposive sampling. Then the researcher found that Class XI IPA 1 consisting of 33 students as experimental-class 1 which was taught by using Discovery learning strategy and Class XI IPA 4 consisting of 31 students as experimental class 2 which was taught by using Inquiry learning strategy. The data collection was conducted by using a study-result test with 15 questions consisting of ten multiple choice questions and five essay questions. The data analysis used two-sample t-test. The result of this research shows tcount ttable that there is no difference of students’ learning result between using Discovery and Inquiry learning strategy in Physics at SMA Negeri 8 Banda Aceh.